2016
DOI: 10.1080/10376178.2016.1235981
|View full text |Cite
|
Sign up to set email alerts
|

Patient advocacy by nurses – past, present and future

Abstract: This paper highlights the gap between the ideal of patient advocacy and the realities of everyday nursing practice. The responsibility for enacting advocacy sits with both individual practitioners and the organizations nurses work within.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 74 publications
0
21
0
7
Order By: Relevance
“…Taking action when safety is endangered by others is considered part of nurses’ ethical responsibilities (International Council Of Nurses ), and patient advocacy has been promoted as part of their core responsibilities (Kalaitzidis & Jewell ). However, nurses may find it difficult to effectively practice patient advocacy and address safety issues (Rainer ; Water et al, ). In their review of qualitative studies, Morrow et al, found that speaking up by nurses is negatively affected by power dynamics and hierarchical constraints, experienced through instances of being ignored, disregarded, or disrespected (Morrow et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Taking action when safety is endangered by others is considered part of nurses’ ethical responsibilities (International Council Of Nurses ), and patient advocacy has been promoted as part of their core responsibilities (Kalaitzidis & Jewell ). However, nurses may find it difficult to effectively practice patient advocacy and address safety issues (Rainer ; Water et al, ). In their review of qualitative studies, Morrow et al, found that speaking up by nurses is negatively affected by power dynamics and hierarchical constraints, experienced through instances of being ignored, disregarded, or disrespected (Morrow et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Possible explanations are that the team from the municipality was from another organisation and that nurses role at the meeting are unclear. Water et al [43] described that nurses sometimes are expected to advocate for their patients in institutional cultures in which they lack authority and have limited power.…”
Section: Discussionmentioning
confidence: 99%
“…Ces situations mobilisent les principes d'advocacy et de justice sociale, qui sont des éléments essentiels à la profession. Malgré leur importance, le sens profond de ces deux principes est actuellement débattu [2] et le risque de rupture identitaire en contexte médico-légal réaffirme l'exigence d'un tel débat. [9] L'advocacy réfère généralement à la défense des intérêts de l'usager et de son bien-être, à son accompagnement au sein du processus décisionnel, ainsi qu'au devoir de soin qui incombe aux infirmières à l'égard des besoins de ce dernier.…”
Section: Penser L'advocacy à Partir De La Justice Socialeunclassified
“…[9] L'advocacy réfère généralement à la défense des intérêts de l'usager et de son bien-être, à son accompagnement au sein du processus décisionnel, ainsi qu'au devoir de soin qui incombe aux infirmières à l'égard des besoins de ce dernier. [1,2] Certains auteurs soulignent l'ambiguïté du sens accordé à ce concept, notamment en raison de sa difficile confrontation à la culture institutionnelle et de la mince frontière séparant ce principe du paternalisme médical. [2] D'autres auteurs ont exposé l'intrication de cette notion au principe de justice sociale, ce qui permet à la pratique infirmière d'aller au-delà d'une approche strictement individuelle afin d'exposer les injustices structurelles pouvant affecter la santé et les droits des usagers.…”
Section: Penser L'advocacy à Partir De La Justice Socialeunclassified
See 1 more Smart Citation